Tinjauan Yuridis Kedudukan Amicus Curiae Terhadap Anak Pelaku Pelecehan Seksual - AAA. Ngurah Tini Rusmini Gorda; I Gusti Bagus Yudas Swastika (UNES Law Review, 2023)
Children as child offender who is not yet 18 years old has been suspected of commiting a criminal act. A criminal act sexual harassment is a crime that is often committed by minors in the form of ex pressions, actions until physical intercourse. So that in this case the concept of “amicus curiae” can help examine and clarify the case of a child perpetrator of sexual harassment in proving a crime. In this studyiaimsutoideterminelthe mechanismsof “amicus curiae” position towards children as perpetrators of sexual harassment and the research method used was normative research method or research using literature study by examing primaryllegalsmaterials, secondary legal materialsand tertiaryylegalsmaterials. So that thehresult ofithis study indicatesthataposition of “amicus curiae” in a criminal act as evidence can be in writing and not in writing. “Amicus Curiae” if it is linked to evidence of article 184 KUHAP ofrthe criminalkproceduremcode, “amicus curiae” can be classified in material evidencetof letter and intructions but not formally. And the concept of amicus curiae canihelp examine and clarify the juvenite criminal justice process as a perpetrator of sexual harassment who is studied from a philosophical, sociological, and juridical perspective by providing a basis for consideration to the judge related to a child perpetrators of sexual harassment and this case the judge can use the concept of a amicus curiae in deciding the sentence for a child perpetrators of sexual abuse by putting forward the best principles for Children without sacrifing children’s rights.